The Prevalence of Helicobacter Pylori in Upper Gastrointestinal Disorders - Baban, Fuad A.; Mohammad, Mohammad O. (Sulaimani Journal for Pure and Applied Sciences, 2003)
Background: Helicobacter pylori are a gram negative spiral bacilli that cause one of the most chronic infection through out the world. Helicobacter pylori infection is associated with many important and serious gastrointestinal diseases like peptic ulcer, chronic gastritis, a known precursor of gastric carcinoma. method: we studied the prevalence of helicobacter pylori infection in a group of patients who presented with various upper G.I discomfort between marches 1997-November 1999. 400 patients were enrolled , they were examined clinically and by upper G.1 endoscopy and 2 piece biopsy were taken from the antrum for rapid wease test for detection of helicobacter pylori infection results : Helicobacter pylori infection is a common infection and for any age group the incidence of infection was more than 60% , pain was the most common presenting symptom (%93), patient harboring ulcer were 88% positive for urease ( 89% in DU, 86% in GU), 72% of patients with endoscopic findings other than ulcer were urease positive and 70% of patients with gastric carcinoma were positive while 64% of patients with negative endoscopy ( non ulcer dyspepsia) were urease positive. Conclusion: infection with helicobacter pylori is common in this community and is strongly associated with an increase risk of peptic ulcer , gastritis and gastric carcinoma however many dyspeptic patients with Helicobacter pylori infection have no endoscopic abnormality ( Functional, non ulcer dyspepsia) we found that urease test is a rapid, cheap and practical test for the detection of Helicobacter pylori infection.
Keywords: Helicobacter pylori; urease test; peptic ulcer